Colorimetric method as alternative to chromium (III) quantification in cattle feces - Alexandra Torres Ospina; Julian Andrés Zapata; Jesus Humberto Gil Gonzalez; Luis Giraldo; Diana Marcela Valencia (Acta Scientiarum. Animal Sciences, 2020)
One of the main factors to establish productivity of grazing cattle is the estimation of forage intake. For this, the most widely used technique is based on the estimation of fecal output using chromium dioxide as external marker. However, quantification can be expensive and sometimes not precise due to the methodology used for this purpose. Therefore, the aim of this study was to validate the colorimetric method for chromium quantification and to implement it in the estimation of fecal output in grazing cattle. The temperature, the digestion time and the wavelength for the measurement were evaluated. The method was validated for selectivity, linearity, detection and quantification limits, precision, accuracy, and stability. Results showed that temperature and digestion time are critical to improve sensitivity and quantification limits. The validation demonstrated that the method is suitable for the quantification of Cr2O3 in a wide range of concentrations, being statistically comparable with a reference method, and offering a reliable low cost and easy to implement alternative, to estimate fecal output in bovine digestibility studies.